Type 2 diabetes mellitus and Alzheimer’s disease in the elderly population: A narrative review - Clementino, Larissa Silva; Matos, Ana Georgia Amaro Alencar Bezerra; Morais, Rian Barreto Arrais Rodrigues de; Camurça, Leonardo Torres; Morais, Patricia Cibelle Leite de; Lorena, Guillermo Cândido de; Morais, Priscila Herbelle Leite de; Lima, Wendryus William de; Versa, Lucas Casarotto; Balensiefer, Douglas Vicente; Gurgel, Genilson Pereira; Paixão, Lara Beatriz Cunha da Silva (Seven Editora, 2024)
Type 2 diabetes has pathological mechanisms similar to those of Alzheimer’s, indicating a correlation between the two conditions. This article aims to present the effects of type 2 diabetes mellitus on the development of Alzheimer’s, emphasizing the molecular mechanisms that correlate these two factors. This study is a qualitative narrative review that aims to comprehensively present the topic "type 2 diabetes mellitus and Alzheimer’s disease in the elderly population". The search was carried out in the virtual libraries PubMed, VHL and Scielo, using keywords and MeSH terms such as "Type 2 Diabetes", "Alzheimer’s Disease" and "Susceptibility to Diseases". The search resulted in 252 articles. After several stages of analysis and selection, 8 relevant articles were chosen to compose the narrative review. The review addresses the relationship between Alzheimer’s and type 2 diabetes, exploring risk factors, common molecular mechanisms, and the role of glucose in neural function. The review indicates a link between type 2 diabetes and Alzheimer’s in the elderly population, with complex biological mechanisms connecting the two conditions. Future research is encouraged to improve patient care. DOI:https://doi.org/10.56238/sevened2024.010-036